MENULIS BAHASA JERMAN MELALUI WHATSAPP MESSENGER UNTUK PESERTA DIDIK KELAS X SMAN 1 GEDANGAN - PUTRI AMANDA, AGUSTIA (LATERNE, 2017)
There are four skills in learning German including listening, reading, speaking and writing. Writing is a complex skill to be mastered as it requires knowledge and idea developments. In writing, the process of thinking in order to develop a written idea and expression is necessary. Furthermore, having a good writing skill, the knowledge of grammar and syntax must be well-possessed. Those make writing uneasy and challenging for most students. To facilitate the students in writing, a media should be used to ease them learning writing in German and communicating with others to create a supportive learning atmosphere. Hereby a social media named Whatsapp was used as a media to discuss the process and the result of learning writing. The research question of this study is how is the result of writing in German through Whatsapp as a social media for the tenth graders of language class SMAN 1 Gedangan? The aim of this study is to describe the result of writing in German through Whatsapp as a social media for the tenth graders of language class SMAN 1 Gedangan. This study belongs to descriptive qualitative study. The data were obtained from students’ writing result in four meetings. They were all analysed based on the writing rubrics.. The result is, in the end of the meeting, students’ writing score is increasing compared with their score in the first meeting. For the writing task given in the last meeting, 3 groups got excellent scores and the rest 2 got good scores. To summarise, Whatsapp as a social media can be used as a media to ease the students write in German in the stage of revising or post writing. Keywords: social media Whatsapp, writing skill.